Axion Inflation and Axion Monodromy from String Theory - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter, we will learn about axion inflation in field theory, how axions appear in string theory, and a specific set-up for string inflation that has been very popular recently, axion monodromy.